Safe Communication in the Implementation of Nursing Care: Level of Knowledge of Nurses about the ISBAR methodology - Ramos, Sara (2022)
Introduction: Scientific evidence proves that the use of standardized and systematized communication minimizes the occurrence of failures that can compromise the safety of care. In Portugal it is standardized that the transmission of information follows the methodology Identification, Current Situation, Background, Evaluation, Recommendation (ISBAR), so it is imperative to produce research on its application and efficiency in health practices. Objective/s: Evaluate the level of knowledge of Portuguese nurses about the ISBAR methodology. Assess the specific training frequency in Communication; Determine the relationship of sociodemographic, academic and professional variables with the level of knowledge of nurses about the ISBAR methodology. Methods: Quantitative, observational study with descriptive analysis and cross-sectional focus, conducted with Portuguese nurses enrolled in the Order of Nurses. Data collection was performed through a Knowledge Questionnaire constructed for the purpose of Ramos and Cunha (2021). The study received a favorable opinion from the Ethics Committee of the Polytechnic Institute of Viseu and the OE that promoted its dissemination between 04/08/2021 and 04/09/2021. Results: We included 142 nurses, representing 0.19% of the universe of nurses enrolled in the EO, mostly female (78.9%). In women the age group is 31-40 years old and in the male gender the age group 51-60 years is predominant. The majority of respondents reported not using the ISBAR methodology (53.5%), with male members using it the most (60.0%). It was found that 80.3% of the elements do not have specific training in «Communication» and of those who have, most have less than 10 hours of training. It was found that academic variables and professional variables influence knowledge about the ISBAR methodology. Conclusion: The safety of care should be an imperative in the art of care. Given that the evidence shows that the frequency of training specifies in communication and particularly on the ISBAR methodology predicts a higher level of knowledge and that 27.5% of participants have a low level of knowledge about the ISBAR methodology it is expected that the adoption of academic curricula with inclusion of these contents, and their training and training, will be able to promote the improvement of care, promote safety and produce gains in Health. Introduction: Scientific evidence proves that the use of standardized and systematized communication minimizes the occurrence of failures that can compromise the safety of care. In Portugal it is standardized that the transmission of information follows the methodology Identification, Current Situation, Background, Evaluation, Recommendation (ISBAR), so it is imperative to produce research on its application and efficiency in health practices. Objective/s: Evaluate the level of knowledge of Portuguese nurses about the ISBAR methodology. Assess the specific training frequency in Communication; Determine the relationship of sociodemographic, academic and professional variables with the level of knowledge of nurses about the ISBAR methodology. Methods: Quantitative, observational study with descriptive analysis and cross-sectional focus, conducted with Portuguese nurses enrolled in the Order of Nurses. Data collection was performed through a Knowledge Questionnaire constructed for the purpose of Ramos and Cunha (2021). The study received a favorable opinion from the Ethics Committee of the Polytechnic Institute of Viseu and the OE that promoted its dissemination between 04/08/2021 and 04/09/2021. Results: We included 142 nurses, representing 0.19% of the universe of nurses enrolled in the EO, mostly female (78.9%). In women the age group is 31-40 years old and in the male gender the age group 51-60 years is predominant. The majority of respondents reported not using the ISBAR methodology (53.5%), with male members using it the most (60.0%). It was found that 80.3% of the elements do not have specific training in «Communication» and of those who have, most have less than 10 hours of training. It was found that academic variables and professional variables influence knowledge about the ISBAR methodology. Conclusion: The safety of care should be an imperative in the art of care. Given that the evidence shows that the frequency of training specifies in communication and particularly on the ISBAR methodology predicts a higher level of knowledge and that 27.5% of participants have a low level of knowledge about the ISBAR methodology it is expected that the adoption of academic curricula with inclusion of these contents, and their training and training, will be able to promote the improvement of care, promote safety and produce gains in Health.